Analysis of The Application of The Muraja'ah Method in The Success of Memorizing The Quran (JUZ 30) - Sayyidah Hana Nafisah; Dede Shandra; Rahmi Yulfa (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2026)
This research is motivated by the low achievement of Al-Quran memorization among students in grade XI-6 at SMA Insan Kamil Bogor, who have not met the target of memorizing 20 verses per week, with an average of only 3–7 verses. This problem is influenced by internal factors such as motivation and boredom, as well as external factors such as time management and academic workload. This study aims to analyze the application of the muraja'ah method in improving the memorization of Al-Quran Juz 30. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation using purposive sampling, involving one T-BTQ coordinator, one teacher, and six students. Data validity was ensured through triangulation of techniques and sources, and analyzed through the stages of data reduction, data display, and conclusion drawing. The results of the study showed that the routine application of muraja'ah, through reading one to two surahs before learning, effectively increased the number of memorized verses. The average memorization improved from 5 verses before the implementation to 23 verses afterward. Supporting factors for this success include familiarity with the Quran and environmental support. Thus, the muraja'ah method has been shown to significantly contribute to improving students’ memorization. Its effectiveness is supported by consistent implementation, evaluation using a memorization logbook, and strong motivation from peers, teachers, and parents.